The Economics of Milkfish Aquaculture in Iloilo, Philippines - Tarrosa-Pestano, Maria Cecilia (1992)
The milkfish (ehanos chanos)industry plays a vital role in the Philippine economy. The industry, however, is facing the problem of low productivity. This study evaluates the efficiency of resource use in milkfish aquaculture. The trans log production and translog prof it functions were estimated using cross-sectional data obtained through a survey of 67 milkfish farmers surveyed in Iloilo, Philippines. In both functions, the explanatory variables were inorganic fertilizer, seed, labour, pesticides,age of pond and respondent's experience. Farm size was entered as dummy variable for small, medium and large farms. The performance of each farm category was evaluated using economic indicators such as rate of return on investment, rate of return on operating cost, ratio of net profit to gross revenues and ratio of net profit to variable costs. The results showed that the small farms had performed better than the other farm groups.